Islam, Seni Musik, dan Pendidikan Nilai di Pesantren - -, Sulasman; Ainusyamsi, Fadlil Yani (PANGGUNG, 2014)
ÃÂ The purpose of this study is to give a description about how the Islam views about art, especially music art. To explain about this purpose, the documentation study is applied in this research. The de- scription is done ontologically, epistemologically, and axiological. For that reasons, we can comprehend what the music is, how characteristic features and ways of working of the music, also we can know how and what for we play music. Furthermore, there will be a new paradigm about music art in the Moslem especially in Pesantren. This research use qualitative method and the result shows that Pesantren as the educational organization of Islam has its own contribution in instilling the values of theological, juri- dical, Islamic socio-cultural, and sophistical. Sphistical value in Pesantren has been put by purpose for cleansing up the soul. To provide the passion and meaning in the context of deepening enlightenment to students performed the internalization of sophistical values in Pesantren through the music. There are diÃ¯Â¬â¬erences about art especially music art in Pesantren between Ulama of Ahlussunah and Ulama of Sufi. Regardless of the controversy between the music is halal or haram, the up growing phenomenon that is there are a many Pesantren which developing the music art. Music in Pesantren is not only just an art but also as a tool of increasing and helping the private and social of Santri.ÃÂ Keywords: Islam, Art, Music, Ulama, PesantrenÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Penelitian ini bertujuan untuk memberi gambaran bagaimana pandangan Islam tentang seni, ÃÂ khususnya Seni Musik. Untuk menjelaskan tujuan ini, maka digunakan studi pustaka. Penjelasan dilakukan secara ontologis, epistemologis, dan aksiologis. Oleh karena itu, kita akan paham tentang musik, bagaimana ciri-ciri dan cara kerja musik, serta tahu alasan dan tujuan kita bermusik. Dengan demikian maka akan lahir paradigma baru tentang seni musik di ka- langan umat Islam khususnya di kalangan pesantren. Metode yang digunakan adalah kualita- tif dan hasil penelitian menunjukan bahwa pesantren sebagai lembaga pendidikan Islam telah berjasa dalam menanamkan nilai-nilai teologia, yuridis, sosio kultural Islam, dan nilai sufistik. Nilai sufistik di pesantren ditanamkan dengan tujuan untuk membersihkan kalbu dari segala kotoran jiwa. Untuk memberikan gairah pendalaman serta pemaknaan dalam rangka pence- rahan jiwa bagi santri dilakukan internalisasi nilai-nilai sufistik di pesantren ÃÂ melalui musik. Terdapat perbedaan pandangan mengenai seni khususnya seni musik dikalangan pesantren yaitu antara ÃÂ ulama ahlusunnah dan ulama sufi. Terlepas dari kontroversi antara halal dan haram nya musik, banyak pesantren yang mengembangkan seni musik. Musik di pesantren selain untuk seni juga dÃÂ³adikan alat untuk ÃÂ meningkatkan dan membantu pribadi dan sosial santri.ÃÂ Kata kunci: Islam, Seni, Musik, Ulama, Pesantren